2015
DOI: 10.1111/jgh.12944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epidermal growth factor receptor protein and gene alteration on Taiwanese hepatocellular carcinomas

Abstract: EGFR CNG was related to crucial clinicopathological features and early recurrence, indicating that EGFR CNG might be a poor prognosis factor for Taiwanese HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that GE11 could mediate passage of conjugated liposomes through the cell membrane [ 34 36 ]. EGFR is overexpressed on the surface of many carcinoma cells, including HCC [ 37 , 38 ]. Therefore, in this study, we crosslinked the GE11 polypeptide to the surface of MS2 VLPs, thus rendering them target EGFR-positive cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GE11 could mediate passage of conjugated liposomes through the cell membrane [ 34 36 ]. EGFR is overexpressed on the surface of many carcinoma cells, including HCC [ 37 , 38 ]. Therefore, in this study, we crosslinked the GE11 polypeptide to the surface of MS2 VLPs, thus rendering them target EGFR-positive cells.…”
Section: Introductionmentioning
confidence: 99%